Fock space multireference coupled cluster theory: study of shape resonance - Bhattacharya, Sumantra; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2013)
The complex absorbing potential along with correlated independent particle potential (CIP) Fock space multireference coupled cluster method is used for the study of resonances. We have studied shape resonance of e(-) - F-2, e(-) - N2O and e(-) -CO molecules. In particular, we have studied e(-) - F-2 scattering at different bond lengths to know whether F-2(-) is bound at the equilibrium bond length of F-2. (C) 2013 Wiley Periodicals, Inc.
Keywords: correlated independent particle potential; Fock-space multireference coupled cluster theory; shape resonance

Excited state geometry optimisation using fock-space multi-reference coupled cluster method - Dutta, Achintya Kumar; Bhattacharya, Sumantra (Molecular Physics, 2014)
The Fock-space multi-reference coupled cluster method is used for the geometry optimisation of the low-lying excited states of the molecules. Molecular geometries of the carbon monohydride cation (CH)(+), water (H2O), ozone (O-3) and formaldehyde (HCHO) in their low-lying excited states are optimised. Excited state gradients are calculated using finite field multi-reference coupled cluster method. We compare our results with other theoretical and/or experimental results, wherever available.
Keywords: adiabatic excitation energy; excited state; Fock-space multi-reference coupled cluster; geometry optimisation; numerical derivative

Shape resonance of sulphur dioxide anion excited states using the CAP-CIP-FSMRCCSD method - Basumallick, Suhita; Bhattacharya, Sumantra; Jana, Irina; Vaval, Nayana; Pal, Sourav (Molecular Physics, 2020)
We have studied the shape resonance of excited states of sulphur dioxide (SO2) anion by using the correlated independent particle Fock space multi-reference coupled cluster (CAP-CIP-FSMRCCSD) method augmented by complex absorption potential. These resonant states have been trapped experimentally in recent years by electron collision. In particular, we have investigated e(-)-SO2 scattering and computed the negative-ion resonance states of the anion responsible for the two resonances around 4.45 and 6.56 eV and compared the results with the existing experimental observations. From the computational results using the CAP-CIP-FSMRCCSD method, it has been observed that both the resonances near 4.45 and 6.56 eV result from A(1) symmetries. [GRAPHICS] .
Keywords: CAP augmented correlated independent particle (CAP-CIP-FSMRCCSD); complex absorption potential (CAP); coupled cluster; Fock space multireference coupled cluster (FSMRCCSD); shape resonance